PENGARUH TEKNOLOGI TERHADAP PEMBENTUKAN ISTILAH BARU DALAM BAHASA ARAB - . Musthofa (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2013)
This paper will describes that Arabic language is one of the world languages that can grow and develop in response to scientific and technological development. In many cases, the growth and development of language can take in part the form of creation of new words. The growth and development of Arabic language, especially inthe form of creation of new words, are heavily influenced by technology, that is because all technologies influences on language, in ways that are not always obvious. In studying language and technology, we will look at how the technology influences on the language use. So when a completely new technology is pased to us, we feel like tryingto learn a new language with it's own syntax and vocabulary. For this reason, we can say that the emerging new technology has its impact on language. In fact, we can easily get new words in dictionaries, for example the new words ة (airplane), ر (train), درا(bicyle), ا (tank), ا (telephone), ا (telegram), (computer), (network, internet), and ة ا (window, for computer) that all of these are old vocabularywith new meaning. So we can get the new words ن !%